1996
DOI: 10.1002/(sici)1097-0045(199610)29:4<243::aid-pros5>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Development of anemia and recovery in prostate cancer patients treated with combined androgen blockade and radiotherapy

Abstract: BACKGROUND The objective of this study was to document previously unreported anemia in prostate cancer patients treated with neoadjuvant combined androgen blockade (CAB) and pelvic radiotherapy (XRT). METHODS Four institutions treated 141 patients (mean age ± SD, 70.9 ± 6.5 years) with zoladex 3.6 mg injection subcutaneous depot monthly and flutamide 250 mg orally three times per day for 2 months (CAB), followed by zoladex and flutamide with concurrent XRT (65–70 Gy) for 7–8 weeks. RESULTS After the XRT, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Asbell et al reported on a multicenter study that demonstrated the development of anemia in 141 patients undergoing CAB 2 months prior to pelvic radiotherapy. Their conclusion was that the anemia was attributable to CAB therapy, as the drop in hemoglobin was much more pronounced than that which is usually seen with radiation therapy to the prostate [89].…”
Section: Anemiasupporting
confidence: 92%
“…Asbell et al reported on a multicenter study that demonstrated the development of anemia in 141 patients undergoing CAB 2 months prior to pelvic radiotherapy. Their conclusion was that the anemia was attributable to CAB therapy, as the drop in hemoglobin was much more pronounced than that which is usually seen with radiation therapy to the prostate [89].…”
Section: Anemiasupporting
confidence: 92%
“…40 Anemia was reported to develop in 81% of patients with prostate cancer after receiving neoadjuvant combined androgen blockade and pelvic radiotherapy. 41 In another study, combined hormonal blockade was associated with a significant decrease in hemoglobin in 90% of patients; this decline was related to the duration of treatment and recovered after treatment of symptomatic patients with recombinant human erythropoietin. 42 In a randomized study of patients with anemia and metastatic hormone-refractory prostate cancer, administration of higher doses of recombinant human erythropoietin was associated with increased hemoglobin, reduction of blood transfusions and improvement in quality of life compared to lower erythropoietin doses.…”
Section: Discussionmentioning
confidence: 96%
“…41 In a prospective study of 147 prostate cancer patients receiving CAB, hemoglobin levels declined significantly in all patients from a mean baseline of 14.9 g dl 21 to means of 13.9, 13.2 and 13.1 g dl 21 at 1, 2 and 3 months, respectively. Hemoglobin levels continued to decline during CAB to a mean nadir of 12.3 g dl 21 at a mean of 5.6 months of CAB, representing a mean absolute hemoglobin decline at nadir of 2.5 g dl 21 .…”
mentioning
confidence: 97%